PELESTARIAN BUDAYA KAULINAN BARUDAK SUNDA DI KAMPUNG BUNGUR DESA JALATRANG KECAMATAN CIPAKU KABUPATEN CIAMIS - Henriyani, Etih; Saepul Hidayat, Eet; Sahadi, Sahadi; Syahril, Dede; Sunarti, Neti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Globalization and digitalization have had a significant impact on the sustainability of local culture, including traditional children's games (Kaulinan Barudak Sunda). The purpose of this study is to determine and analyze the supporting factors and inhibiting factors in the preservation of the Sundanese kaulinan barudak culture in Bungur Village, Jalatrang Village, Ciamis Regency. This study used a qualitative approach, with data collection techniques through field studies and literature review. The results indicate that the Kaulinan Barudak Sundanese tradition persists through community support, village educational tourism programs, and the involvement of schools and cultural activists. This traditional game contains social, moral, educational, and cultural values ​​that are important for the character and identity development of the younger generation. However, challenges such as the dominance of digital games, limited resources, and a lack of long-term policy support remain major obstacles. Therefore, a local Penta Helix collaboration involving the village government, cultural communities, educational institutions, academics, and the community is needed for contextual and sustainable cultural preservation.